Influência do uso do intervalo HSV na capacidade de diferenciação da variável visual cor em mapas corocromáticos visualizados em meio digital - Monyra Guttervill Cubas; Tony Vinicius Moreira Sampaio (Confins)
Technological advances have turned printed maps into maps that are produced and disseminated in digital environment. Digital maps allow, among other things, changes in symbology, data values ​​and scale of visualization. This change demanded the investigation of some of the theoretical foundations that were the basis for thematic maps production. In particular, those who guided the use of color visual variable, since it implied changes in the way it was obtained (from subtractive to additive system) and means of dissemination (from paper to electronic devices). This research analyzes the ability of color differentiation in digital maps since there were changes in HSV intervals (Hue, Saturation and Value). The results demonstrate that color perception did not proportionally follows HSV intervals. Chromatic maps visualized in digital media do not always allow users, especially those in teaching process, to correctly differentiate the themes present in them. Finally, results reinforced the need to use perceptually uniform color spaces for production of chorochromatic maps and indicated that the ability to differentiate colors in digital environment is similar to that already observed in printed maps.